The importance of non-technical skills in accounting graduates - Ismail, Noor Azizi; Elham, Faisol; Abdul Manaf, Kamarul Bahrain (Universiti Utara Malaysia Press, 2000)
The purpose of this study is to look at the quality issue from the perspective of one of the most important customers of higher education institutions-employers that hire the accounting graduates.Specifically, this study determines how well skill requirements match skill preparedness of accounting graduates.Results revealed that. five most important non-technical skills required by employers were the ability to perform assigned tasks, having initiative, teamwork, computer literacy, and problem solving.Employers, however; perceived that higher education institutions do not seem to prepare accounting graduates with all the skills required.The majority of employers agree that quality differences exists between accounting graduates ,from public and private institutions, and accounting graduates with and without professional qualifications.Finally, the study highlights suggestions to improve the quality of accounting graduates, and also recommendations for future research.